Limite jurisdicional e a manutenção da integridade da ordem desportiva - Garcia, Vitor de Checchi (2024)
The present study aims to analyze the connection between the Sportive Order and the Public Order, specifically regarding the points of intersection between these two systems, resulting in the formation of the National Sportive Order for the organization and management of competitive sports and the development of public politics for the national sports, as well as some of the diverging points between these Orders, resulting on the practical analysis of each case and the ponderation in applying the dispositions of one Order over the other one, considering the content and the limits of each rule. Regarding the National Sportive Order and public politics for sports, this study will analyze the evolution of the Brazilian laws for sport and the modernization of the various sportive movements and its organizations, presenting the different ways that the competitive sports organizations were developed in Brazil, considering the many legal changes throughout the years and the legal protections for this private movement Also, it will be presented the concept of the “sportive jurisdiction” as the capacity of the Sportive Order in creating organizations capable of judging cases of relevance for the sportive movement. About the sportive jurisdiction, this study will approach its relations with the state jurisdiction, the connection between them throughout the “Sports Justice” – the system established to judge disciplinary and championship infractions – and the confrontation of the two jurisdictions, resulting in the creation of organizations by both of them with the capacity to resolve conflicts (and the effects of the decisions presented by each jurisdiction)